THE EFFECT OF REGIONAL FINANCIAL PERFORMANCE ON REGIONAL FINANCIAL INDEPENDENCE IN THE PROVINCE OF CENTRAL JAVA - Bernadetta U Paradintya; Hafidz Habibillah Fauzi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This research was conducted to determine how a city or district area can be independent in financing all government operational activities without depending on the central government. This study aims to determine the factors that affect regional independence. This research is also used for evaluation in government financial management and decision-making for stakeholders in investing by seeing whether the area is independent or not. The research uses quantitative method based on secondary data, including data from the Central Statistics Agency (BPS) of Central Java Province in 2019, stating the number of districts as 29 and cities as many as 6 cities in Central Java. The sample selection used in this study used a purposive sampling technique where the data used in this study contained data from the 2015-2019 Regional Government Financial Reports. Data analysis uses panel data regression with data application processing, namely Eviews 10. The results of this study reveal several variables that affect regional financial independence; namely, efficiency ratios that have a positive effect on regional independence, capital expenditure compatibility ratios that have a positive impact on regional financial independence, and effectiveness ratios that have a positive effect on the level of regional financial independence. Meanwhile, the variable that does not affect the level of regional independence is operating expenditure.